Pengaruh Work Family Enrichment terhadap Work Engagement pada Ibu Bekerja yang Memiliki Anak Disabilitas - Tiffany Ibrahim; Dinda Dwarawati (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Work engagement is a motivational construct, a positive state, and being fully involved in one's work which is characterized by vigor, dedication and absorption (Schaufeli et al., 2002). Work family enrichment is the extent to which an individual's experience in one role can improve the quality of life in another role (Greenhaus & Powell, 2006). The aim of this research is to determine the effect of Work Family Enrichment on Work Engagement in Working Mothers who Have Disabled Children which refers to the Work Family Enrichment theory from Greenhaus & Powell (2006) and the Work Engagement theory from Schaufeli & Bakker (2002). This research uses quantitative causality research methods with a sample of 101 working mothers who have children with disabilities. The data analysis technique uses multiple linear regression tests. To measure Work Engagement using the Utrecht Work Engagement Scale-9 (UWES-9) by Schaufelli & Bakker (2003). Meanwhile, to measure Work Family Enrichment, we use the measurement scale from Carlson et al., (2006). The research results show that the Work Family Enrichment value has an influence of 16.2% on Work Engagement. The direction of Family-Work Enrichment involvement has the greatest influence, namely 12.26%, on Work Engagement, with the affect dimension being the dimension that has the greatest influence, namely 7.94%. Abstrak. Work engagement merupakan suatu konstruk motivasional, keadaan positif, dan secara penuh terlibat pada pekerjaannya yang ditandai dengan adanya vigor, dedication dan absorption (Schaufeli et al., 2002). Work family enrichment merupakan sejauh mana pengalaman individu pada suatu peran dapat meningkatkan kualitas hidup pada satu peran lainnya (Greenhaus & Powell, 2006). Tujuan dari penelitian ini untuk mengetahui pengaruh work family enrichment terhadap work engagement pada ibu bekerja yang memiliki anak disabilitas yang mengacu pada teori work family Enrichment dari Greenhaus & Powell (2006) dan teori work engagement dari Schaufeli & Bakker (2002). Penelitian ini menggunakan metode penelitian kuantitatif kausalitas dengan sampel sebanyak 101 orang ibu bekerja yang memiliki anak disabilitas. Teknik analisis data menggunakan uji regresi linear berganda. Untuk mengukur Work Engagement menggunakan Utrecht Work Engagement Scale-9 (UWES-9) oleh Schaufelli & Bakker (2003). Sedangkan untuk mengukur Work Family Enrichment menggunakan skala pengukuran dari Carlson et al., (2006). Hasil penelitian menunjukkan nilai work family enrichment memberikan pengaruh sebesar 16.2% terhadap work Engagement. Arah keterlibatan family-work enrichment memberikan pengaruh terbesar yaitu 12.26% terhadap work engagement dengan dimensi affect sebagai dimensi yang memberikan pengaruh terbesar yaitu 7.94%.